Optimal Incentives for Patent Challenges in the Pharmaceutical Industry - Enrico Böhme; Severin Frank; Wolfgang Kerber (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Patent settlements in the pharmaceutical industry between originator and generic firms have been scrutinized critically by competition authorities for delaying the market entry of generics and being therefore potentially anticompetitive. In this paper we present a model that analyzes the tradeoff between limiting the delaying of generic entry through patent settlements and giving generic firms more incentives for challenging weak patents of the originator firms. We can show that under general assumptions allowing patent settlements with a later market entry of generics than the expected market entry under patent litigation would increase consumer welfare. We introduce a policy parameter for determining the optimal additional period for collusion that would maximize consumer welfare and show that the size of this policy parameter depends on the size of the challenging costs, the intensity of competition, and the duration between the market entries of the first and second generic.
Keywords: L10; L40; O34; 330